1980
DOI: 10.1128/jvi.33.3.976-982.1980
|View full text |Cite
|
Sign up to set email alerts
|

Coding assignments of double-stranded RNA segments of SA 11 rotavirus established by in vitro translation

Abstract: The segmented double-stranded (ds) RNA genome of the simian rotavirus SA 11, after denaturation, can be translated in a cell-free protein synthesizing system. Of the 11 genome segments, 9 can be resolved on polyacrylamide gels and thus could be individually isolated and translated, providing a means of identifying the polypeptide encoded by each segment. On the basis of electrophoretic mobility of products in sodium dodecyl sulfate-polyacrylamide gels, the probable gene-coding assignments of dsRNA segments 1 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
88
1

Year Published

1983
1983
1994
1994

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 36 publications
12
88
1
Order By: Relevance
“…This was to be expected since previous studies by Bastardo et al, Killen and Dimmock, and Matsuno and Inouye had shown that hyperimmune monospecific antiserum to the 38-kd glycoprotein neutralizes rotavirus (1, 21,24). The demonstration that this protein is the product of the eighth or ninth gene confirms our genetic data (15) and supports the translation studies of others (23,25,27). Despite the fact that the 38-kd glycoprotein is not the viral hemagglutinin, monoclonal antibody directed at it exhibited HI activity.…”
Section: Discussionsupporting
confidence: 92%
“…This was to be expected since previous studies by Bastardo et al, Killen and Dimmock, and Matsuno and Inouye had shown that hyperimmune monospecific antiserum to the 38-kd glycoprotein neutralizes rotavirus (1, 21,24). The demonstration that this protein is the product of the eighth or ninth gene confirms our genetic data (15) and supports the translation studies of others (23,25,27). Despite the fact that the 38-kd glycoprotein is not the viral hemagglutinin, monoclonal antibody directed at it exhibited HI activity.…”
Section: Discussionsupporting
confidence: 92%
“…on August 5, 2020 by guest http://iai.asm.org/ Downloaded from well-defined segments. Apart from this, it has been shown elsewhere (1,12,13,19) that each one of the 11 viral RNA segments codes for a particular polypeptide. Thus, any segment decay, either enzymatic or nonspecific, would be likely to prevent efficient virus infectivity or replication (or both).…”
Section: Discussionmentioning
confidence: 91%
“…Recent extensive serological studies indicate that rotaviruses have two distinct antigenic specificities: subgroup and serotype specificities [Kapikian et al, 19811. Subgroup specificity has been detected by the enzyme-linked immunosorbent assay (ELISA) [Zissis and Lambert, 19801, complement fixation test [Zissis and Lambert, 19781, immune adherence hemagglutination assay (IAHA) [Kapikian et al, 19811, and immune electron microscopy (IEM) [Zissis and Lambert, 19781, and is associated with a major component of inner capsid (42,000-dalton protein; 42K protein), which is coded by the sixth gene segment [Mason et al, 1980;Smith et al, 1980;Greenberg et al, 1983a1, while serotype specificity is defined by the virus neutralization test [Kapikian et al, 19811 and is associated with outer capsid protein (34K to 37K protein) which the eighth or ninth gene segment codes for McCrae and McCorquodale, 1982;Greenberg et al, 1983bl. To date, two subgroups of human rotaviruses (HRVs) and four serotypes have been found Urasawa et al, 1982;Wyatt et al, 19831. Until 1981, the only HRV, with the exception of rescued viruses obtained by genetic reassortment between fastidious HRVs and ts mutants of cultivable bovine rotavirus [Greenberg et al, 1981, 19821, that could grow in cell culture was the Wa strain obtained by multiple serial passage in gnotobiotic piglets [Wyatt et al, 19801.…”
Section: Introductionmentioning
confidence: 99%